(untitled) (Research, Society and Development, 2020)
Objective: The objective of this study was to describe and compare the predictive factors for the risk of preterm births in the cities of Belém and Recife in the North and Northeast regions of Brazil. Methodology: This is a cross-sectional and sectional study of preterm births in the North and Northeast of Brazil, with preliminary data from the year 2016, available in the database of the Live Birth Information System. Results: The study sample consisted of 5,530 prematurely born residents in the Metropolitan Region of Recife, together with 4,152 born prematurely, living in the Metropolitan Region of Belém, for a total of 9,682. Conclusion: This study sought to understand the determinants of premature births in two Brazilian municipalities, whose different and particular socioeconomic contexts in each municipality presented good social and health indicators, allowing us to deduce that such municipalities present interventions in the scope of public health with a view to improving the condition and quality of life of the population/individual, since such determinants may represent risks of a different magnitude than those observed in less developed regions.